The Reliability of Parkour Skills Assessment - Martin Dvořák; Jiří Baláš; Andrew J. Martin (MDPI AG, 2018)
The aim of the study was to determine the reliability of parkour skills assessment in field conditions. Twenty young men completed three trials of a parkour obstacle course on two separate days. The tested group consisted of 10 beginners (age 16 ± 1 years, body mass = 65 ± 12 kg, height = 177 ± 7 cm) and 10 advanced traceurs (age 18 ± 2 years, body mass = 68 ± 14 kg, height = 178 ± 6 cm). The performance was video-recorded and subsequently analyzed by three raters (total score 0-45). Median and percentiles were used to characterize results from all sessions by all raters. Inter-rater, intra-session and inter-session reliability were assessed using Krippendorff's α for ordinal data. The Mann-Whitney test was used to assess the differences between beginners and advanced traceurs. Advanced traceurs obtained a total score from 41 to 44 whilst beginners achieved 27 to 33 points. Krippendorff's α for total score ranged from 0.910 to 0.916 between raters, 0.828 to 0.874 between trials, and from 0.839 to 0.924 between days. The proposed parkour course differentiated two different ability levels and the skills assessment demonstrated excellent reliability between raters, trials, and days.